7 - The Other Side of the Story: The Costs of Being a Public Good Academic - Ndaba, Mthobisi (Journal of Higher Education in Africa, 2022)
This article argues that the relationship between higher education and the public good should be understood not only from a macro-level point of view, in terms of how higher education systems and institutions contribute to the public good. It should also be understood from a micro-level point of view. Drawing on a qualitative study of the role of academics in higher education’s contribution to the public good, this article demonstrates that micro-level- focused research allows for a deeper and richer insight into the intricacies of this relationship. It does this from the vantage point of the costs of being a public good academic, as recounted by fifteen academics from two universities in South Africa. The perceptions of these academics indicate that the costs of producing public good at universities in South Africa are more than just the financial costs covered by student fees, government subsidies and donor funding. They include relational, psychological and career-related costs, as well as those related to personal resources and identity contingencies, which academics must deal with in advancing the public good. This article concludes that further micro-level-focused research can uncover more nuanced aspects of the complex relationship between higher education and the public good.